Inscription on a pillar within the Mahamandapa (pillared hall) - Temples of India Project Team (Jio Institute, 2024)
The inscription dated 1174 CE (VS 1231) commences with the words Deva shri Gokarllanaghvasi, reaffirming the deity’s name as Gokarna Deva. It is inscribed on a pillar within the mahamandapa (pillared hall) of the temple, alongside other informative inscriptions.